The Mouse Levator Auris Longus Muscle: An Amenable Model System to Study the Role of Postsynaptic Proteins to the Maintenance and Regeneration of the Neuromuscular Synapse - Ojeda, Jorge; Bermedo-García, Francisca; Pérez, Viviana; Mella, Jessica; Hanna, Patricia; Herzberg, Daniel; Tejero, Rocío; López-Manzaneda, Mario; Tabares, Lucia; Henríquez, Juan Pablo (Frontiers in Cellular Neuroscience, 2020)
The neuromuscular junction (NMJ) is the peripheral synapse that controls the coordinated movement of many organisms. The NMJ is also an archetypical model to study synaptic morphology and function. As the NMJ is the primary target of neuromuscular diseases and traumatic injuries, the establishment of suitable models to study the contribution of specific postsynaptic muscle-derived proteins on NMJ maintenance and regeneration is a permanent need. Considering the unique experimental advantages of the levator auris longus (LAL) muscle, here we present a method allowing for efficient electroporation-mediated gene transfer and subsequent detailed studies of the morphology and function of the NMJ and muscle fibers. In addition, we have standardized efficient facial nerve injury protocols to analyze LAL muscle NMJ degeneration and regeneration. Our results show that the expression of a control fluorescent protein does not alter either the muscle structural organization, the apposition of the pre- and post-synaptic domains, or the functional neurotransmission parameters of the LAL muscle NMJs; in turn, the overexpression of MuSK, a major regulator of postsynaptic assembly, induces the formation of ectopic acetylcholine receptor clusters. Our NMJ denervation experiments showed complete reinnervation of LAL muscle NMJs four weeks after facial nerve injury. Together, these experimental strategies in the LAL muscle constitute effective methods to combine protein expression with accurate analyses at the levels of structure, function and regeneration of the NMJ.